PIBM 1.0: an individual-based model for simulating phytoplankton acclimation, diversity, and evolution in the ocean - I. Sala; I. Sala; B. Chen (Geoscientific Model Development, 2025)
Phytoplankton is a diverse group of photosynthetic organisms and accounts for almost half of global primary production. However, most existing marine ecosystem models incorporate limited phytoplankton diversity, overlook phytoplankton evolution, and treat phytoplankton as concentrations instead of particles. Here we present an individual-based phytoplankton model that captures three dimensions of phytoplankton traits (size, temperature, and light affinities) and allows phytoplankton cells to mutate in a one-dimensional (1D) water column. Other ecosystem components include dissolved inorganic nitrogen, 20 zooplankton size classes, and detritus, all modeled as Eulerian fields. This hybrid plankton model can not only reproduce the general seasonal patterns of nutrients, chlorophyll, and primary production in the subtropical ocean, but also simulate variations in phytoplankton traits and functional diversity. We expect that this model will be a useful tool for studying phytoplankton physiology, diversity, and evolution in the ocean.